Neuroimaging and clinical outcomes of oral anticoagulant-associated intracerebral hemorrhage - Tsivgoulis, Georgios; Purrucker, Jan; Rizos, Timolaos (Annals of neurology, 2018)
Objective Whether intracerebral hemorrhage (ICH) associated with non-vitamin K antagonist oral anticoagulants (NOAC-ICH) has a better outcome compared to ICH associated with vitamin K antagonists (VKA-ICH) is uncertain. Methods We performed a systematic review and individual patient data meta-analysis of cohort studies comparing clinical and radiological outcomes between NOAC-ICH and VKA-ICH patients. The primary outcome measure was 30-day all-cause mortality. All outcomes were assessed in multivariate regression analyses adjusted for age, sex, ICH location, and intraventricular hemorrhage extension. Results We included 7 eligible studies comprising 219 NOAC-ICH and 831 VKA-ICH patients (mean age = 77 years, 52.5% females). The 30-day mortality was similar between NOAC-ICH and VKA-ICH (24.3% vs 26.5%; hazard ratio = 0.94, 95% confidence interval [CI] = 0.67-1.31). However, in multivariate analyses adjusting for potential confounders, NOAC-ICH was associated with lower admission National Institutes of Health Stroke Scale (NIHSS) score (linear regression coefficient = −2.83, 95% CI = −5.28 to −0.38), lower likelihood of severe stroke (NIHSS > 10 points) on admission (odds ratio [OR] = 0.50, 95% CI = 0.30-0.84), and smaller baseline hematoma volume (linear regression coefficient = −0.24, 95% CI = −0.47 to −0.16). The two groups did not differ in the likelihood of baseline hematoma volume < 30cm3 (OR = 1.14, 95% CI = 0.81-1.62), hematoma expansion (OR = 0.97, 95% CI = 0.63-1.48), in-hospital mortality (OR = 0.73, 95% CI = 0.49-1.11), functional status at discharge (common OR = 0.78, 95% CI = 0.57-1.07), or functional status at 3 months (common OR = 1.03, 95% CI = 0.75-1.43). Interpretation Although functional outcome at discharge, 1 month, or 3 months was comparable after NOAC-ICH and VKA-ICH, patients with NOAC-ICH had smaller baseline hematoma volumes and less severe acute stroke syndromes. Ann Neurol 2018;84:702-712
Gesehen am 12.06.2019